The Histological and Immunopathological Landscape of Lung Autopsy Sample of COVID 19: The landscape of Lung Autopsy Sample of COVID 19 - Sardar Saleh, Lana (Cellular and Molecular Biology, 2023)
The purpose of this study is to explain the reason for the death histologically by comparing normal lungs with infected ones. The lung autopsy samples were taken from 12 adult patients in Erbil forensic medicine diagnosed before with covid 19 which also consider a reason for death. For histological examinations and the identification of SARS-CoV-2 RNA, autopsy materials were collected, fixed in 4% neutral formaldehyde for at least 24 hours, and sampled as formalin-fixed, paraffin-embedded (FFPE) tissues. Staining with hematoxylin and eosin (H&E) was done in accordance with protocol. Based on the results of immunopathology in deceased people, it was shown that there was a strong positive reaction with BCL2 antibody in the cytoplasm of lung alveolar cells compared to the lungs of healthy people. Also, a positive reaction with catenin antibody, SMA antibody had occurred in the cytoplasm of lung alveolar cells in the lungs of patients, and finally, it was shown that the Vimentin antibody reaction was present in the cytoplasm of lung alveolar cells of patients. All four investigated factors, BCL2, catenin, SMA antibody and vimentin antibody, have played an important role in the inflammation and fibrosis of lung tissue in patients with COVID, and the combination of these four factors together has played a significant role in worsening the symptoms and worsening of the disease.